Physicochemical characteristics of cold-pressed blackcurrant-, strawberry-, and raspberry seed oils during storage and its influence on thermo-oxidative stability - Yolanda Victoria Rajagukguk; Mahbuba Islam; Anna Grygier; Aleksander Siger; Magdalena Rudzińska; Jolanta Tomaszewska-Gras (NFS Journal)
The storage characteristics of cold-pressed blackcurrant-, strawberry- and raspberry seed oils and the factors influencing thermo-oxidative stability during storage were determined. It was established that throughout one year there were no significant (p ≤ 0.05) changes of thermo-oxidative stability (OIT at 120 and 140 °C) and fatty acid composition in all berry seed oils (BSO), despite a minor reduction in antioxidant activity (DPPH radical scavenging) and tocopherol content, and an increase in acid value, p-anisidine value, and K232, K268 values. Pigment degradation became noticeable after 6 months, resulting from a decrease in chlorophyll and carotenoid content, and observed in changes of colour parameters (angle hue, chroma, ΔE). The study also showed that many compositional factors play an important role in maintaining the thermo-oxidative stability of berry seed oils at a constant level over a period of one year, among which the most significant parameters influencing OIT values were the content of fatty acid c18:1, tocopherols and carotenoids, as revealed by the multiple linear regression analysis (MLR).